THE TEACHING OF THE TOPIC 'CULTURE OF THE PEOPLES OF CENTRAL ASIA IN THE FIRST HALF OF THE 16TH–19TH CENTURIES' THROUGH THE METHOD OF GROUP DISCUSSION - Vohidov Sardorbek Bahodir o‘g‘li (Bright Mind Publishing, 2025)
This article highlights the cultural life of the peoples of Central Asia during the 16th to the first half of the 19th century, including their achievements in science, literature, architecture, crafts, and religious-enlightenment activities. Special attention is given to the importance of using the "collaborative discussion" method to help students study this historical period more deeply. The advantages of the method, its application stages in the teaching process, and the expected outcomes are analyzed.
Keywords: Central Asia, culture, 16th–19th centuries, collaborative discussion, pedagogical method, historical education, interactive methods.